STRATEGI GURU PAI DALAM PENGAJARAN PENDIDIKAN AGAMA ISLAM PADA MASA PANDEMI COVID 19 DI SEKOLAH DASAR - Yahya, Safarudin (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
This study aims to determine the steps or strategies of PAI teachers in teaching Islamic religious education in elementary schools at SDN 3 Baubau. The method used in this research is qualitative. This type of qualitative research was chosen to describe and analyze phenomena, events, and learning activities at the research location. The research findings show: The teacher's strategy in teaching Islamic religious education at SDN 3 Koa Baubau is implemented by implementing an integrative learning system, namely distance (online) and close distance or face-to-face (offline). The distance teaching method was chosen as an alternative amid efforts to prevent the spread of COVID-19. In its implementation, the delivery of teacher material uses platform-based information technology media such as the WhatsApp application, Google Classroom and Zoom Meeting. Furthermore, offline or direct learning is carried out in order to anticipate students who have limitations in internet operational costs. Of course, the implementation of offline learning is carried out in rotation while still implementing very strict health protocols. In addition, the teacher gives additional assignments to students and asks parents to be actively involved in controlling the assigned tasks and participate in informing about student activities during the pandemic at home.